Factors Associated with Households’ Awareness of Social Health Insurance in Sundarharaicha Municipality, Morang, Nepal - Yadav, Arun Kumar; Poudel, Kshitij (DEPAN, 2025)
Background: Out-of-pocket payment for health care is a major challenge in developing countries like Nepal, often leading to financial hardship and delays in treatment, particularly among poor and marginalized populations. To address these challenges, the Government of Nepal implemented the Social Health Insurance (SHI) program. The aim of the program is to improve financial protection and ensure equitable access to quality health services. Despite its potential, limited research has focused on households’ awareness of SHI, especially in eastern Nepal. Objectives: This study aimed to assess awareness of households towards the Social Health Insurance program and identify key socio-demographic and health-related factors associated with it in Sundarharaicha Municipality, Morang, Nepal. Material and Methods: A cross-sectional study design was employed in three wards of Sundarharaicha Municipality in Morang district, covering households newly enrolled, those who renewed, and those without SHI membership. Primary data was collected from 392 households using a structured questionnaire. Descriptive analysis, chi-square tests, and Firth’s penalized binary logistic regression were used to analyze relationships among awareness and socio-demographic variables. Internal consistency of the awareness measures was assessed using Cronbach’s alpha. Results: The majority of respondents (71.7%) revealed high awareness of SHI, with reliable awareness scales (Cronbach’s alpha = 0.93). From bivariate analysis, awareness was significantly associated with variables such as ward, gender, age, marital status, family type, ethnicity, religion, and history of chronic disease, source of knowing (p < 0.05). Firth’s logistic regression identified ward, ethnicity, family health history, and source of information as key determinants of awareness. Conclusion: This study identified factors associated with household awareness towards social health insurance (SHI). Firth’s logistic regression analysis identified ward of residence, ethnicity, family health history, and source of information as the key determinants of awareness.